Quantifying the wave attenuation of hybrid seagrass-reef structures – An experimental study - Xihang Xu; M. Salauddin (Coastal Engineering, 2027)

Influence of canopy fragmentation and spacing on seagrass-induced wave attenuation - Xihang Xu; M. Salauddin (Estuarine, Coastal and Shelf Science, 2026)

Numerical modelling of wave overtopping behind an eco-retrofitted vertical seawall using OpenFOAM® - Xihang Xu; J. Keenahan; M. Salauddin (Ocean Engineering, 2026)

Wave attenuation by artificial reef balls with varying oyster coverage density for coastal protection: A laboratory study - H. Ghasemi; V. Jakaus; B. Rice; P.R. Brooks; J.J. O'Sullivan; A. Dastgheib; M. Salauddin (Ocean Engineering, 2026)

Advancing wave overtopping prediction at eco-engineered Seawalls: Integrating laboratory experiments and machine learning - M.A. Habib; S. Abolfathi; J.J. O'Sullivan; P.R. Brooks; M. Salauddin (Ocean Engineering, 2025)

Quantifying wave attenuation by seagrass: a comprehensive review of assessment techniques - Xihang Xu; M. Salauddin (Frontiers in Marine Science, 2025)
Seagrasses, often referred to as ecosystem engineers, play a vital role in shallow coastal waters worldwide. They can not only provide key ecological benefits such as ecosystem restoration and carbon sequestration, but also offer significant engineering benefits, including sediment stabilization and wave energy dissipation. Despite its potential biological benefits, the mechanisms behind seagrass-induced wave attenuation remain inadequately understood. Furthermore, inconsistencies in the recorded metrics complicate the comparison of findings across various experimental studies. This study aims to address these challenges by thoroughly examining six key parameters for assessing the wave attenuation performance of seagrass meadows: wave energy dissipation, drag coefficient, wave transmission coefficient, wave attenuation coefficient, wave-induced flow velocity, and turbulent kinetic energy. By systematically reviewing the most relevant lab-based experimental studies conducted from 2000 to 2024, this study summarises the developments, applications, and performance of these key parameters in analysing seagrass-induced wave dissipation, discussing the physical mechanism behind. The effects of currents on seagrass-induced wave attenuation performance are also investigated. The findings of this work provide a foundation for conducting a unified framework to assess the impact of canopy features and wave characteristics on seagrass-induced wave attenuation, further contributing to the development of coastal protection policies in combination with seagrass restoration guidance.

Impact of wave dynamics and turbulence on stratosphere-troposphere exchange of ozone during convective events - Salauddin Mohammad; P Vinay Kumar; Syu-Ruei Jhang; M Venkat Ratnam; Gopa Dutta (Journal of Atmospheric and Solar-Terrestrial Physics, 2025)

Distinct amino acid substitutions in the EEV glycoprotein and DNA-dependent RNA polymerase of lumpy skin disease virus identified in wetland areas of Bangladesh - Moslema Jahan Mou; S.M. Nazmul Hasan; Anandha Mozumder; Marjana Akter; Riyan Al Islam Reshad; Roni Mia; Md. Salauddin; M. Shaminur Rahman; Md. Mahmudul Alam; Sharmin Akter; Sukumar Saha; Tofazzal Islam; et al. (Research in Veterinary Science, 2025)

Whole-Genome Analysis of Multidrug-Resistant Klebsiella pneumoniae Kp04 Reveals Distinctive Antimicrobial and Arsenic-Resistance Genomic Features: A Case Study from Bangladesh - Md. Javed Foysal; Farhana Momtaz; A. M. Masudul Azad Chowdhury; Afroza Akter Tanni; Asma Salauddin; Md. Zahid Hasan; Sohana Akter Mina; Nahid Sultana; Sanjoy Kanti Biswas; Kamrul Islam; Alfred Tay; Adnan Mannan (Current Microbiology, 2025)

Improved prediction of wave overtopping rates at vertical seawalls with recurve retrofitting - S. Dong; M. Salauddin; S. Abolfathi; J.M. Pearson (Ocean Engineering, 2024)

Oncoinformatic screening of the gene clusters involved in the HER2-positive breast cancer formation along with the in silico pharmacodynamic profiling of selective long-chain omega-3 fatty acids as the metastatic antagonists - A K M Helal Morshed; Salauddin Al Azad; Md. Abdur Rashid Mia; Mohammad Fahim Uddin; Tanzila Ismail Ema; Rukaiya Binte Yeasin; Sanjida Ahmed Srishti; Pallab Sarker; Rubaita Younus Aurthi; Farhan Jamil; Nure Sharaf Nower Samia; Partha Biswas; et al. (Molecular Diversity, 2023)

Data-driven approaches in predicting scour depths at a vertical seawall on a permeable shingle foreshore - M. Salauddin; D. Shaffrey; M. A. Habib (Journal of Coastal Conservation, 2023)
Despite recent research efforts in advancing machine learning (ML) tools to predict nearshore characteristics at sea defences, less attention has been paid to ML algorithms in predicting scouring characteristics at vertical seawalls. In this study, four ML approaches were investigated, including gradient boosting decision trees (GBDT), random forest (RF), support vector regression (SVR), and ridge regression (RR). These approaches were utilised to predict scour depths at the toe of an impermeable vertical seawall in front of a permeable shingle slope. The developed ML algorithms were trained and tested (70% for training and 30% for testing) using the scouring datasets collected from laboratory tests performed on seawalls in a 2D wave flume at the University of Warwick. A novel hyperparameter tuning analysis was performed for each ML model to tailor the underlying dataset features while mitigating associated data overfitting risks. Additionally, the model training process demonstrated permutation feature importance analysis to reduce overfitting and data redundancy. The model predictions were compared with the observed values using the coefficient of determination ( R 2 ) score, root mean square error (RMSE), and Pearson correlation R -value. Consequently, the RF and GBDT methods accurately predicted scour depths at the toe of vertical seawalls with shingle foreshores. This study produced data, information, and a model that could directly or indirectly benefit coastal managers, engineers, and local policymakers. These benefits included forecasting scour depths and assessing the impact on the structural integrity of the sea defences in response to the threat imposed by extreme events, which are essential for the sustainable management of coastal protections and properties behind such structures in coastal areas.

Target-specificity of different amyrin subunits in impeding HCV influx mechanism inside the human cells considering the quantum tunnel profiles and molecular strings of the CD81 receptor: a combined in silico and in vivo study - Anika Jabin; Mohammad Fahim Uddin; Salauddin Al Azad; Ashfaque Rahman; Fawzia Tabassum; Pritthy Sarker; A K M Helal Morshed; Samiur Rahman; Fatima Fairuz Raisa; Musfiqur Rahman Sakib; Abeer Hasan Olive; Tabassum Islam; et al. (In Silico Pharmacology, 2023)

Seasonal effects of atmospheric waves over tropical tropopause using radiosonde observations at Hyderabad, India - Salauddin Mohammad; Gopa Dutta; M. C. Ajay Kumar; P. V. Rao; P. Vinay Kumar; Krishna Ette (Meteorology and Atmospheric Physics, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Eco-Engineering of Seawalls—An Opportunity for Enhanced Climate Resilience From Increased Topographic Complexity - Md Salauddin; John J. O’Sullivan; Soroush Abolfathi; Jonathan M. Pearson (Frontiers in Marine Science, 2021)
In the context of “green” approaches to coastal engineering, the term “eco-engineering” has emerged in recent years to describe the incorporation of ecological concepts (including artificially water-filled depressions and surface textured tiles on seawalls and drilled holes in sea structures) into the conventional design process for marine infrastructures. Limited studies have evaluated the potential increase in wave energy dissipation resulting from the increased hydraulic roughness of ecologically modified sea defences which could reduce wave overtopping and consequent coastal flood risks, while increasing biodiversity. This paper presents results of small-scale laboratory investigations of wave overtopping on artificially roughened seawalls. Impulsive and non-impulsive wave conditions with two deep-water wave steepness values (=0.015 and 0.06) are evaluated to simulate both swell and storm conditions in a two-dimensional wave flume with an impermeable 1:20 foreshore slope. Measurements from a plain vertical seawall are taken as the reference case. The seawall was subsequently modified to include 10 further test configurations where hydraulic effects, reflective of “eco-engineering” interventions, were simulated by progressively increasing seawall roughness with surface protrusions across three length scales and three surface densities. Measurements at the plain vertical seawall compared favorably to empirical predictions from the EurOtop II Design Manual and served as a validation of the experimental approach. Results from physical model experiments showed that increasing the length and/or density of surface protrusions reduced overtopping on seawalls. Benchmarking of test results from experiments with modified seawalls to reference conditions showed that the mean overtopping rate was reduced by up to 100% (test case where protrusion density and length were maximum) under impulsive wave conditions. Results of this study highlight the potential for eco-engineering interventions on seawalls to mitigate extreme wave overtopping hazards by dissipating additional wave energy through increased surface roughness on the structure.

Assessment of biogas generation potential from slaughterhouse wastes in Dhaka city, Bangladesh - Sayedus Salehin; Syed Shaheer Uddin Ahmed; Md. Ehasanul Hoque; Md. Salauddin Mrigdad; S. M. Ashef Hussain; S. M. Tahsin Intisar (Waste Disposal & Sustainable Energy, 2021)

Experimental Study on Toe Scouring at Sloping Walls with Gravel Foreshores - M. Salauddin; J. M. Pearson (Journal of Marine Science and Engineering, 2019)
Sea defences, such as urban seawalls can fail due to the development of a scour hole at the toe of the structure. The scour depth or the information on ground levels at the structure toe is required for the sustainable management of coastal defences, due to its influence on the structural performance. This research reports and summarises the main findings of a new laboratory study on toe scouring at a smooth sloping wall with permeable gravel foreshore. A set of small-scale laboratory experiments of wave-induced scouring at sloping seawalls were conducted. Two gravel sediments of prototype d50 values of 13 mm and 24 mm were used to simulate the permeable 1:20 (V:H) gravel beach configurations in the front of a smooth 1 in 2 sloping wall. Each experiment comprised of a sequence of around 1000 random waves of a JONSWAP energy spectrum with a peak enhancement factor of 3.3. The relationship of the scour depth with toe water depth, Iribarren number, and wall slope were investigated from the test results of this work and through a comparison with available datasets in the literature. The results of this study showed that the relative toe water depth and Iribarren number influence the relative toe scour depth at a sloping structure on a shingle beach. Within the experimental limitations, the maximum toe scour depths were observed for the experiments under spilling and plunging wave attack.

Impact of cyclone Nilam on tropical lower atmospheric dynamics - P. Vinay Kumar; Gopa Dutta; M. V. Ratnam; E. Krishna; B. Bapiraju; B. Venkateswara Rao; Salauddin Mohammad (Advances in Atmospheric Sciences, 2016)